PENGARUH PELATIHAN DAN PENDIDIKAN, PENGALAMAN KERJA DAN PARTISIPASI MANAJEMEN PADA EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Widyantari, Ni Wayan Lisna; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
This research aimed to determine the effect of training and educational programs, personal work experience and participation in the management of Usage Effectiveness of Accounting Information Systems. The theory used in this research is the theory of Technology Acceptance Model (TAM) The population in this study were all LPD in the district of Ubud as many as 32 LPD. This study using purposive sampling method. The data collected by interviews, questionnaires and documentation. The data analysis used is multiple linear regression analysis. The results showed that the training and education programs, work experience and management participation has  positive influence on the effectiveness of the use of Accounting Information Systems (LPD studies in Ubud sub district). Results of the analysis showed that their training and education programs, personal work experience, and management's participation will be more effective in the use of accounting information systems to produce an update.
Keywords: training and education programs; personal work experience; the participation of management; the effectiveness of the use of accounting information systems